Antagonistic and plant growth promotion of rhizobacteria against Phytophthora colocasiae in taro - Kelbessa, B.G.; Ghadamgahi, F.; Kumar, P. Lava; Ortíz, R.; Whisson, S.C.; Bhattacharjee, Ranjana; Vetukuri, R.R. (Frontiers Media, 2022)
Taro leaf blight caused by Phytophthora colocasiae adversely affects the growth and yield of taro. The management of this disease depends heavily on synthetic fungicides. These compounds, however, pose potential hazards to human health and the environment. The present study aimed to investigate an alternative approach for plant growth promotion and disease control by evaluating seven different bacterial strains (viz., Serratia plymuthica, S412; S. plymuthica, S414; S. plymuthica, AS13; S. proteamaculans, S4; S. rubidaea, EV23; S. rubidaea, AV10; Pseudomonas fluorescens, SLU-99) and their different combinations as consortia against P. colocasiae. Antagonistic tests were performed in in vitro plate assays and the effective strains were selected for detached leaf assays and greenhouse trials. Plant growth-promoting and disease prevention traits of selected bacterial strains were also investigated in vitro. Our results indicated that some of these strains used singly (AV10, AS13, S4, and S414) and in combinations (S4+S414, AS13+AV10) reduced the growth of P. colocasiae (30−50%) in vitro and showed disease reduction ability when used singly or in combinations as consortia in greenhouse trials (88.75−99.37%). The disease-suppressing ability of these strains may be related to the production of enzymes such as chitinase, protease, cellulase, and amylase. Furthermore, all strains tested possessed plant growth-promoting traits such as indole-3-acetic acid production, siderophore formation, and phosphate solubilization. Overall, the present study revealed that bacterial strains significantly suppressed P. colocasiae disease development using in vitro, detached leaf, and greenhouse assays. Therefore, these bacterial strains can be used as an alternative strategy to minimize the use of synthetic fungicides and fertilizers to control taro blight and improve sustainable taro production.